The association of maternal nutrition and children's pre-primary experience with over-age attendance in secondary school: evidence from lowland Nepal. (2020) - Marphatia, Akanksha A.; Wells, Jonathan C.K.; Reid, Alice M.; Borja, Mario Cortina; Manandhar, Dharma S.; Sen, Aman; Saville, Naomi; Devakumar, Delan; Osrin, David; Prost, Audrey; Dulal, Sophiya
Highlights: Over-age attendance is increasing but remains under-studied in South Asia. Children fall behind by entering pre-primary or primary late, and by repeating a grade during/after primary school. Rural location, thin and uneducated mothers predicted late pre-primary entry. Educational research and interventions need to focus on the earlier time-point of pre-primary. Improving maternal nutrition and education may ensure timely progression of children in school.